Nazariyyah al-Tarakhus wa Tatbiqatiha ’Inda al-Imam al-Syatibi - Naseh Alwan, Ammar Abdullah (Jurnal Fiqh, 2010)
There is no dispute on the fact that Imam Shatibi is the originator of the higher purposes of the Islamic law and perhaps there was ample benevolence in the delay of formulating the purposes of Islamic law until seventh century according to Islamic calendar. Imam Shatibi grew up in an era when Andalusia was about to fall at the hands of Spaniards which means that the Muslims were in the age of decline and weakness and far from the spirit of Islamic legislation. This made Imam Shatibi while formulating the subject of the purposes of the Islamic law to consider the outside factors beyond the purposes of the legislation, perhaps most significantly; his contemporary society was generally away from the purposes and objectives of the legislation, and purposes of fatwa and the difference of opinions among the jurists. The flame upon which the people of the whims depended in disputation and concessions was a fundamental one as the difference of opinion is permissible without considering what that would lead to whimsical and prejudicious proponents of the juristic schools of thought which finally could in a practical way turn away from the purposes of the Islamic shariah. That is why Imam Shatibi set forth theories and principles which illustrate and describe the purposes of Islamic law.